Eksplorasi Pemanfaatan Aplikasi Canva dalam Meningkatkan Kecerdasan Visual Spasial Anak Usia Dini di Raudhatul Athfal Am-Mentari Kota Jambi - Madyan Madyan; Dewanti Apriliana; Bunga Permata Sari; Witdia Witdia (Lembaga Pengembangan Kinerja Dosen, 2025)
This explorative research was conducted to comprehensively explore and describe the utilization of the Canva application as an effective digital learning medium in efforts to enhance the visual-spatial intelligence of early childhood. Visual-spatial intelligence, which includes the ability to understand spatial relationships, manipulate mental imagery, and solve visual problems, is an essential foundation for children's learning readiness. This study adopted a qualitative approach with a descriptive case study method located at RA Am-Mentari Jambi City. Data were collected through structured observation techniques regarding children's interaction with the Canva application, semi-structured interviews with educators, and in-depth analysis of the digital portfolios produced by the children. The research subjects involved classroom teachers and a group of children aged 5-6 years. The results of the exploration indicate that the utilization of Canva creates an active and child-centered learning environment. The graphic design features available in Canva (such as drag and drop, layering, and object scale adjustment) were employed by teachers as targeted stimulation. This utilization successfully improved children's abilities in: a) Arranging and organizing visual elements (layout), b) Recognizing and differentiating shapes, sizes, and orientations (visual discrimination), and c) Representing their ideas and imagination into two-dimensional forms (spatial representation). The conclusion of this study is that the Canva application not only serves as a tool but also as a creative platform that significantly facilitates the enhancement and refinement of the aspects of visual-spatial intelligence in early childhood. The implementation of Canva provides an innovative alternative to traditional methods in developing this cognitive domain